Generalization of the quantitative stress-intensity relationship of mechanoluminescent sensor SrAl2O4:Eu2+, Dy3+ in an elastic domain. (14th June 2019) - Guo, Songtao; Cai, Tao; Zhao, Xiaofeng; Peng, Di; Xiao, Ping; Wang, Weizhe; Liu, Yingzheng
Abstract: The quantitative relationship between stress and mechanoluminescence (ML) intensity ratio in an elastic domain was established in SrAl2 O4 :Eu 2+, Dy 3+ (SAOED) resin samples. The stress on the resin sample (macro stress) was directly measured and the stress on the SAOED (micro stress) was calculated by the Eshelby method. The macro and micro stresses keep a linear relationship, and the ML intensity ratio is proportional to stress. Even though the relationship between macro stress and ML intensity ratio is dependent on SAOED concentration and the elastic modulus of the matrix, a universial relationship exists between the micro stress and ML. Based on these results, a generalized equation, which could describe the relationship between the stress, ML intensity and ML sensor matrix, was established, which can then be applied in situations of different SAOED concentrations or even different matrix materials. This generalized relationship could provide guidance for the development and application of SAOED-based ML sensors.